PENGEMBANGAN MODUL PEMBELAJARAN IPA TERPADU BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK SMP/MTs KELAS VII - Khuryati Khuryati; Ika Kartika (Kaunia: Integration and Interconnection Islam and Science, 2014)
This study is aimed to (1) develop an integrated-science module based on Contextual Teaching and Learning (CTL) for SMP/MTs grade VII; (2) examine the quality of the integrated-science module developed; (3) examine the response of students to the integrated- science module developed. This study is research and development (R & D) with procedural model that adapts the research and development procedure according to 4-D (Define, Design, Develop, and Disseminate) model. The research instrument is a checklist form of quality assessment sheet using a Likert scale and a checklist form questionnaire responses of students using a Guttman scale. The data was analyzed by descriptive quantitative. The results of this study: (1) integrated-science module based on Contextual Teaching and Learning (CTL) for SMP/MTs grade VII, (2) the quality of integrated-science module that have been developed according to content experts, media experts, and teachers are very good with ideal percentages respectively 82.4%, 83.3% and 90.1%, (3) the response of students in small-scale field trials and large scale is agreed with ideal percentages respectively 82.9% and 83.8%. The results of this study indicate that the integrated-science module based on Contextual Teaching and Learning (CTL) that has been developed can be used as one of science learning materials.